2021
DOI: 10.32322/jhsm.913654
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum perlecan levels in pregnancy with mild and severe preeclampsia

Abstract: Aim: To determine the levels of perlecan contributing to angiogenesis and autophagy inhibition in severe and mild preeclamptic women. Material and Method:The study included a total of 89 patients as 3 group including severe preeclampsia as group 1 (n:30), mild preeclampsia as group 2 (n:30), and control as group 3 (n:29). All the groups were evaluated in terms of prepartum maternal serum perlecan levels.Results: The Perlecan level of the group 1 was at higher levels than others (p<0.0001). The Perlecan level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It seems that the maintenance of a certain stable concentration in blood has a regulatory effect on central hemodynamics of pregnant women. This conclusion is supported by the study of Erkayıran et al, 2021, who concluded that HSPG2 has a protective effect during pregnancy and is a physiologically important molecule for the continuity of the physiological functions in pregnancy [ 57 ]. Although this study had a different design, and it was found that the HSPG2 level increased in the severe preeclampsia group in proportion to systolic and diastolic blood pressure, liver and kidney function tests [ 57 ], the authors did not link these effects with eGC damage.…”
Section: Discussionmentioning
confidence: 76%
“…It seems that the maintenance of a certain stable concentration in blood has a regulatory effect on central hemodynamics of pregnant women. This conclusion is supported by the study of Erkayıran et al, 2021, who concluded that HSPG2 has a protective effect during pregnancy and is a physiologically important molecule for the continuity of the physiological functions in pregnancy [ 57 ]. Although this study had a different design, and it was found that the HSPG2 level increased in the severe preeclampsia group in proportion to systolic and diastolic blood pressure, liver and kidney function tests [ 57 ], the authors did not link these effects with eGC damage.…”
Section: Discussionmentioning
confidence: 76%